Unsustainable vs. Sustainable Hunting for Food in Gabon: Modeling Short- and Long-Term Gains and Losses - Wilkie, David S.; Wieland, Michelle; Poulsen, John R. (Frontiers in Ecology and Evolution, 2019)
Today, rural people continue to consume wild animals (aquatic and terrestrial) because they are often cheaper and more available than farmed livestock and fish. In many places where the meat from wild animals is an important source of food and income for poor rural families, the capture, consumption or trade of wild animals is illegal and remains within the informal sector and outside of national accounting and regulatory systems. Few studies exist to help policy makers and wildlife managers develop and implement systems designed to halt unsustainable hunting, prevent species loss, and maintain, over the long term, flows of wildlife available to people as a source of food and income. This paper uses empirical data from a tropical forest area in Gabon within a heuristic simulation model to explore how hunter capture rates would need to change over time to halt unsustainable hunting and to maximize the nutritional and economic value of wildlife as a source of food and income over the long term. Results show that sustainable hunting of wildlife populations that are at or near 50% of carrying capacity (0.5K) generates more biomass available for consumption and income generation over 25 years than either hunting to maintain current population densities or continuing to hunt unsustainably. Unsustainable hunting generates more biomass than sustainable hunting but only for the first 1 to 3 years after which offtake dwindles rapidly. Achieving sustainable hunting will require that hunters reduce their offtake for 3-13 years until depleted populations recover, which may be unlikely unless they have access to alternative sources of food and income.